The Influence of Principal Leadership and Teachers’ Motivation on Students’ Ability in Elementary Schools - Hernawati Hernawati; Syarwani Ahmad; Yessi Fitriani (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examines the influence of principal leadership and teacher motivation on student academic abilities at the elementary school level in Sumber Marga Telang District, an area with geographical constraints. Employing a quantitative survey design, data were collected from a simple random sample of teachers and students using Likert-scale questionnaires for leadership and motivation, and academic grade documentation for student ability. Multiple linear regression, t-tests, and F-tests were applied for analysis. Results reveal that both principal leadership and teacher motivation significantly affect student abilities, both partially and simultaneously. The coefficient of determination (R² = 0.62) indicates that these two variables explain 62% of the variance in student outcomes, with the simultaneous test further confirming the model’s robustness (F-count 15.87 > F-table 3.10). The novelty lies in contextualizing these relationships within a geographically limited setting, where systemic support is often scarce. Practically, the findings underscore the urgent need for sustained investment in principals’ managerial capacity and teachers’ motivational welfare as strategic levers for educational quality improvement. The study contributes empirical evidence from an under-researched rural context, reinforcing that human capital factors in school leadership are pivotal to student success, and offers actionable insights for policymakers aiming to elevate basic education outcomes in similar underserved regions.